Faktor-Faktor yang Mempengaruhi Loyalitas Konsumen di Siloam Hospitals Kebon Jeruk dan Lippo Village - Franzeska Olivia Indra Putri; Chintya Nur; Margaretha Pink Berlianto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Background: Customer loyalty is a major factor for all industries, including in service industry. One of the service industries is the healthcare industry. In the healthcare industry today, there’s a change approach from paternalistic (doctor-led) to patient-centered. In patient-centered approach, the patient participates for the decision of the services they will receive. If the services matched with the patient’s needs, the patient will trust and use the services again in the future, hence, will increase patient’s loyalty. The purpose of this study was to determine the effect of service quality, customer trust, and customer value on customer loyalty at the JCI standardized Siloam Hospitals.Method: Data collection in this study was conducted using an online questionnaire to 166 people who had visited Siloam Hospitals Kebon Jeruk and Lippo Village using simple random sampling method. Analysis using partial lease square-structural equation modeling (pls-sem) was carried out using the SmartPLS program to analyse the data.Results: The findings from the study are that all the variables, which are service quality (interaction quality, physical environment quality, outcome quality), customer value and customer trust, have a positive relationship to customer loyalty at Siloam Hospitals Kebon Jeruk and Lippo Village.